Criminalization Policy in Residential Decrees and Synchronization With the Codified Criminal Law - Teguh Prasetyo (Jurnal Hukum IUS QUIA IUSTUM, 2009)
The synchronization of criminal provisions in the residential decrees with the codified criminal law has not yet been made due to variety of legal sources to which residential decrees may refer. Among the differences which synchronization are the difference in the provisions of witnesses and also the difference in the interpretation made by the regulatorsKeywords: Policy, criminalization, Local Government Regulation, synchronization.